2016
DOI: 10.1039/c6ra17212a
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt assisted morphological changes of cationic gemini surfactant (12-4-12) micelles

Abstract: pH and concentration dependent growth of gemini surfactant (12-4-12) micelles in the presence of bile salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The most widespread bile salts considered in recent reports are cholate, deoxycholate and taurodeoxycholate. Sodium cholate is known for its capability to act as a transdermal enhancer [ 84 ] and additive to mono- and dicationic surfactant solutions significantly modifying their morphological behavior [ 85 ] and release profile of cargo encapsulated in self-assembled drug nanovehicles [ 86 ]. Sodium deoxycholate was reported as part of biamphiphiles, ionic compounds with both cationic and anionic amphiphilic nature, which aggregate shape could be accurately controlled [ 87 ]; micellar catalyst for the synthesis of 1,2,3-triazole derivatives; their characteristics is superior in comparison with those of conventional surfactants CTAB and Triton-X-100 [ 88 ].…”
Section: Self-assembly Of Amphiphilic Compoundsmentioning
confidence: 99%
“…The most widespread bile salts considered in recent reports are cholate, deoxycholate and taurodeoxycholate. Sodium cholate is known for its capability to act as a transdermal enhancer [ 84 ] and additive to mono- and dicationic surfactant solutions significantly modifying their morphological behavior [ 85 ] and release profile of cargo encapsulated in self-assembled drug nanovehicles [ 86 ]. Sodium deoxycholate was reported as part of biamphiphiles, ionic compounds with both cationic and anionic amphiphilic nature, which aggregate shape could be accurately controlled [ 87 ]; micellar catalyst for the synthesis of 1,2,3-triazole derivatives; their characteristics is superior in comparison with those of conventional surfactants CTAB and Triton-X-100 [ 88 ].…”
Section: Self-assembly Of Amphiphilic Compoundsmentioning
confidence: 99%
“…The fascinating phase behavior of such mixed systems arises due to the interplay of the electrostatic interaction, hydrophobic interaction, H-bonding, and steric effect. The interaction of SAILs with cationic, , anionic, , nonionic, , Gemini, , Pluronic, and Tetronic , surfactants has been investigated by several researchers. The synergistic interaction in the mixed systems comprising 1-dodecyl-3-methylimidazolium chloride (C 12 mimCl) with the nonionic surfactant Triton X-100 or Triton X-405 has been reported by Farahani et al and it was revealed that micellization is spontaneous in nature and more favorable in the presence of Triton X-100.…”
Section: Introductionmentioning
confidence: 99%